Modifikasi Kumbang Koksi sebagai Ide Penciptaan Motif Batik Digital pada Media Mug Menggunakan Teknik Digital Printing - Putri Ananda; Raden Burhan Surya Nata Diningrat (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Indonesia has a rich cultural heritage, one of which is batik, which has become a national cultural heritage and is recognized by UNESCO as a world intangible cultural heritage. Along with the development of digital technology and the increasingly dynamic needs of society, innovations in the form of digital batik have emerged, opening new opportunities in the preservation and development of traditional batik motifs. Digital batik not only allows efficiency in the production process but also expands the reach of creative expression through the exploration of new, more modern forms, colors, and media. This creative research aims to explore the shape and color of the female beetle (Coccinellidae) as inspiration in creating digital batik motifs that are then applied to mugs using digital printing techniques. The method used is exploratory with an artistic practice approach, involving stages ranging from visual concept design, digital sketching, color exploration, to the printing process on ceramic media. The design process was carried out digitally using the Ibis Paint application on a mobile device, which demonstrates that batik works can be created flexibly with the help of simple technology. The results of this creation are 15 digital batik works with the visual character of the female beetle that have been artistically modified without losing their distinctive shape and striking color. Each design measures 20 x 8 cm and is printed on a cylindrical mug with a curved surface. This research demonstrates that natural elements such as insects can be a rich source of aesthetic inspiration for developing contemporary batik motifs. Furthermore, this work demonstrates that modern technology can play a crucial role in maintaining the relevance and appeal of traditional arts like batik in the era of globalization and digitalization.